2018
DOI: 10.12691/ajmr-6-3-2
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Tea Tree oil against Pathogenic Bacteria and Comparison of Its Effectiveness with Eucalyptus Oil, Lemongrass Oil and Conventional Antibiotics

Abstract: Tea Tree oil (TTO) is known to have antibacterial effects and this study was aimed to determine the abilities to control pathogenic bacteria and also compared the antimicrobial effectiveness of Eucalyptus oil (ECO), Lemongrass oil (LGO) and antibiotics those are using for bacterial infection. This study of antimicrobial activity against ten pathogenic bacteria: Staphylococcus aureus, Streptococcus pyogenes, Pseudomonas aeruginosa, Proteus vulgaris, Aeromonas hydrophila, Escherichia coli, Streptococcus pneumoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…However, the lowest MIC and MBC values (16.0 and 256.0 μg/mL, respectively) were detected against the S. aureus strain ( Table 2 ). Similar results were reported by Mumu and Hossain [ 39 ], who mentioned that EO showed maximum (100%) inhibition activity against S. aureus , P. vulgaris and A. hydrophila. On the other hand, Aldoghaim et al [ 40 ] stated that Eucalyptus oils showed variable antimicrobial activity against the tested microorganisms and A. baumannii was the most sensitive microorganism, followed by S. enterica Typhimurium and E. coli , while the MIC index proved the cidal effect of Eucalyptus oil [ 40 ].…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…However, the lowest MIC and MBC values (16.0 and 256.0 μg/mL, respectively) were detected against the S. aureus strain ( Table 2 ). Similar results were reported by Mumu and Hossain [ 39 ], who mentioned that EO showed maximum (100%) inhibition activity against S. aureus , P. vulgaris and A. hydrophila. On the other hand, Aldoghaim et al [ 40 ] stated that Eucalyptus oils showed variable antimicrobial activity against the tested microorganisms and A. baumannii was the most sensitive microorganism, followed by S. enterica Typhimurium and E. coli , while the MIC index proved the cidal effect of Eucalyptus oil [ 40 ].…”
Section: Resultssupporting
confidence: 90%
“…The possible potent antimicrobial mechanisms underlying the observed susceptibility can be explained by the differences in the outer membrane composition of the tested microorganisms [46]. Another possibility is the presence of certain oil components such as 1,8-cineole which can increase the permeability of the cytoplasmic membrane [39]. Behbahani et al [47] studied the antimicrobial activities of carboxy methyl cellulose (CMC) films containing different Eucalyptus camaldulensis leaf extracts against some pathogens and reported that aqueous and alcoholic extracts were quite effective at a 2000 µg/mL concentration against Streptococcus pyogenes and Staphylococcus epidermidis.…”
Section: Antimicrobial Activity Of the Prepared Nanofibersmentioning
confidence: 99%
See 1 more Smart Citation
“…The tea tree oil microemulsion prepared according to our previous publications [3] According to previous reports, the antibacterial and antifungal activities of the preparations were evaluated using agar well diffusion methods [4]. Each plate of agar contained microemulsion and conventional emulsioncontaining Tea Tree Oil and 3% Tween as a surfactantpreparations incorporated into different gelling agents to examine the activity of the preparations against Propionibacterium acnes, Staphylococcus aureus, and Candida albicans.…”
Section: Methodsmentioning
confidence: 99%
“…The agar diffusion method is commonly used as a quick test to determine the potential susceptibility or resistance to an antibiotic. The results can be compared with those of Mumu (2018) [25], where inhibition zones were observed by TTO against clinical bacterial isolates after 24 h of incubation. Although the study shows that TTO is effective against both Gram-positive and Gram-negative strains, our study found inhibition values higher than those found in this study for S. aureus isolates.…”
Section: Biological and Antioxidant Activity Of Free Tto 321 Antimicr...mentioning
confidence: 99%